READING DOWN OF ART 370 AND 35A-2019 IN JAMMU AND KASHMIR: A CASE OF OFFENSIVE LAWFARE - Chitalkar, Sonali; Chimurkar, Rahul; Tiwari, Vimlok (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The State of JKL is populated by diverse populations and is composed of different regional identities. This has reflected in differing political aspirations in all three regions. This paper discusses how the different aspirations of three regions have been used in the Great game. It is established how Jammu has historically expressed an urge for autonomy from influences in Kashmir. It has also always been the voice for constitutional parity with the rest of the nation. Kashmir on the other hand has found a space for ethno-centric aspirations and these have been historically articulated by a closed political circle which has used these aspirations as tool for power. The paper establishes how, the reading down of Article 370 and Art 35A was a classic case of offensive legal warfare (lawfare) to move against big power geopolitical games played through regional proxies like Pakistan.